3D reconstruction based on compressed-sensing (CS)-based framework by using a dental panoramic detector. Issue 1 (January 2016) - Je, U.K.; Cho, H.M.; Hong, D.K.; Cho, H.S.; Park, Y.O.; Park, C.K.; Kim, K.S.; Lim, H.W.; Kim, G.A.; Park, S.Y.; Woo, T.H.; Cho, S.I.
Highlights: Practical two functionalities of dental panoramic and cone-beam CT features are studied. The compressed-sensing (CS) framework is employed. An efficient CS-based reconstruction algorithm for the proposed geometry is implemented. It is proposed to develop a cost-effective, low-dose, volumetric dental X-ray imaging system. Abstract: In this work, we propose a practical method that can combine the two functionalities of dental panoramic and cone-beam CT (CBCT) features in one by using a single panoramic detector. We implemented a CS-based reconstruction algorithm for the proposed method and performed a systematic simulation to demonstrate its viability for 3D dental X-ray imaging. We successfully reconstructed volumetric images of considerably high accuracy by using a panoramic detector having an active area of 198.4 mm × 6.4 mm and evaluated the reconstruction quality as a function of the pitch ( p ) and the angle step ( Δθ ). Our simulation results indicate that the CS-based reconstruction almost completely recovered the phantom structures, as in CBCT, for p ≤ 2.0 and θ ≤ 6 °, indicating that it seems very promising for accurate image reconstruction even for large-pitch and few-view data. We expect the proposed method to be applicable to developing a cost-effective, volumetric dental X-ray imaging system.